Gut Microbiota Interacts with Markers of Adipose Tissue Browning, Insulin Action and Plasma Acetate in Morbid Obesity. Issue 3 (29th December 2017) - Moreno‐Navarrete, José María; Serino, Matteo; Blasco‐Baque, Vincent; Azalbert, Vincent; Barton, Richard H.; Cardellini, Marina; Latorre, Jèssica; Ortega, Francisco; Sabater‐Masdeu, Mònica; Burcelin, Rémy; Dumas, Marc‐Emmanuel; Ricart, Wifredo; et al.
Abstract : Scope: To examine the potential relationship among gene expression markers of adipose tissue browning, gut microbiota, and insulin sensitivity in humans. Methods and results: Gut microbiota composition and gene markers of browning are analyzed in subcutaneous (SAT) and visceral (VAT) adipose tissue from morbidly obese subjects ( n = 34). Plasma acetate is measured through 1 H NMR and insulin sensitivity using euglycemic hyperinsulinemic clamp. Subjects with insulin resistance show an increase in the relative abundance (RA) of the phyla Bacteroidetes and Proteobacteria while RA of Firmicutes is decreased. In all subjects, Firmicutes RA is negatively correlated with HbA1c and fasting triglycerides, whereas Proteobacteria RA was negatively correlated with insulin sensitivity. Firmicutes RA is positively associated with markers of brown adipocytes ( PRDM16, UCP1, and DIO2 ) in SAT, but not in VAT. Multivariate regression analysis indicates that Firmicutes RA contributes significantly to SAT PRDM16, UCP1, and DIO2 mRNA variance after controlling for age, BMI, HbA1c, or insulin sensitivity. Interestingly, Firmicutes RA, specifically those bacteria belonging to the Ruminococcaceae family, is positively associated with plasma acetate levels, which are also linked to SAT PRDM16 mRNA and insulin sensitivity. Conclusion: Gut microbiota composition is linked to adipose tissue browning and insulin action in morbidly obese subjects, possibly through circulating acetate. Abstract : This figure indicates the association among Ruminococcaceae family, plasma acetate levels, SAT expression of browning‐related genes and insulin sensitivity, suggesting that increased Ruminococcaceae ‐enhanced acetate biosynthesis might promote SAT browning and systemic insulin sensitivity in morbidily obese subjects.